Pengembangan Media Sembung Ukara Berbasis Kearifan Lokal Pada Mata Pelajaran PPKn Kelas IV di SD Negeri 2 Karanggintung - Mafida Syifa' Fauziyah; Aji Heru Muslim (Departement of Mathematics Education, 2024)
Instructional media is expected to serve as a means to preserve the culture present in society, as education incorporating local wisdom in schools plays a significant role in providing positive experiences for students. It aims to instill great aspirations such as ensuring safety and addressing various social dynamics in the future, one of which is achieved by developing and utilizing instructional media based on local wisdom. This study aims to develop and determine the feasibility of the Sembung Ukara instructional media based on local wisdom. The research employs the RD method with the ADDIE model. Data collection techniques include interviews, observations, questionnaires, and documentation. The results of data analysis are reflected in the product validation outcomes by media and subject matter experts. The media expert validation yielded a score with a percentage of 70%, while the subject matter expert validation scored 91.43%. Both scores fall into the valid category, indicating that the Sembung Ukara media can be used in the instructional process. The research results, based on responses from teachers and students, show that the scores obtained fall into the highly attractive category, with 100% from teacher responses and 97% from student responses. Thus, it can be concluded that the Sembung Ukara instructional media received positive feedback from both teachers and students.